The effect of antibiotics on swine carcasses - Soule, R.P. Jr.; Mackintosh, D.L.; Richardson, D.; Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
The two antibiotics fed in these four trials were Aureomycin and Terramycin HCl at the level of 10 mg. per pound of total ration. Lot 1 pigs were the controls receiving the basal ration; Lot 2, basal plus 10 mg. of Aureomycin HCl per pound of total feed; Lot 3, basal plus 10 mg. of Terramycin HCl per pound of total feed. Fifty-two pigs were used in the four trials carried out from November 1952 to October 1954. The pigs were slaughtered at the college laboratory when they reached approximately 225 pounds. The stomach and intestinal contents were weighed and subtracted from the live slaughter weight to determine the net body weight. All carcasses were weighed after 48 hours chill at 34 ̊F. The length of body was measured from the anterior portion of the first rib to the anterior portion of the aitch bone. The back fat is the average of the three measurements-opposite the first rib, last rib, and last lumbar vertebra. The primal cuts are the skinned ham, trimmed loin, N.Y. style shoulder, and the trimmed belly. The lean cuts are the skinned ham, trimmed loin, and N.Y. style shoulder. The primal and lean-cut yields were based on net body weight and chilled carcass weight. The carcasses were graded, using the average back fat thickness and length as criteria for grades. These grades are based on the official U.S. Standards for Grades of Pork Carcasses, which are choice 1, 2, 3; medium; and cull.
Keywords: Swine; Terramycin HCl; Aureomycin; Carcass; Dressing percentage